MINORITAS MUSLIM THAILAND Asimilasi, Perlawanan Budaya dan Akar Gerakan Separatisme - Yuniarto, Paulus Rudolf (Jurnal Masyarakat dan Budaya, 2005)
The aim of this article is to describe Thailand Moslem minority with problem of assimilation, culture resistance and the root of separatist movement. One challenges that facing Thailand multiethnic people and Thai country today is management about diversity of ethnicity development. The characteristic of Thai multiethnic people strive for government attention especially related with crucial problem had been facing; ethnicity conflict and the rise up of communalism, separatism, and problem majority-minority relation. Composition of this problem in fact has related each others. The down fall of Thailand politics integration and obligation to accept Thai monolithic ethnic identity can be seen in anarchy demeanor of Moslem Patani to Thai government and claim for independencies Southern Thailand territorial separates from nation state of Thailand. The impact from integration process in the Thailand state building on Moslem area is create unstable relation between ethnic majority-minority, resources distribution and economics injustice form, the worn out of center government and local government democratic relation, social politics economic and culture polarizes. Stakeholder role like civil society organization (CSO), government, and military failed to take an integration policy program or conflict resolution.